2016
DOI: 10.5010/jpb.2016.43.2.240
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for high-frequency transgenic shoot regeneration viaAgrobacterium tumefaciensin flax (Linum usitatissimumL.)

Abstract: In this study, routinely used transformation method, which includes transferring explants onto co-cultivation medium after inoculating them with bacterial solution for a while, was compared with 3 different inoculation methods. In every 3 methods, hypocotyl explants excised from 7-day-old sterile flax seedlings having cotyledon leaves and no root system dried under air flow in sterile cabin for 35 min were inoculated with different volumes of bacterial solution at different inoculation periods. GV2260 line of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…In addition to this protocol, different positions of the hypocotyl region from 7-day-old sterile seedlings were used. That was why the transformation efficiency in our study (93.54%) was found to be higher than the 84.19% in the study by Beyaz et al (5).…”
Section: Resultscontrasting
confidence: 54%
See 3 more Smart Citations
“…In addition to this protocol, different positions of the hypocotyl region from 7-day-old sterile seedlings were used. That was why the transformation efficiency in our study (93.54%) was found to be higher than the 84.19% in the study by Beyaz et al (5).…”
Section: Resultscontrasting
confidence: 54%
“…In the study conducted by Beyaz et al (5), the mean transformation efficiency was reported to be 30.45% in the routine inoculation method in which hypocotyl explants excised from 7-day-old sterile flax seedlings were directly inoculated with a 500 μL bacterial solution for 20 minutes. In the newly described inoculation method, the highest mean transformation efficiency was found to be 84.19%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study conducted by Beyaz et al [58], the aim was to increase transformation efficiency in flax (Linum usitatissimum L.) by increasing osmotic pressure of the tissue as plant material flax cultivars "Madaras," "Clarck," and "1886 Sel." were used in the study.…”
Section: Utilizing Explant's Negative Atmospheric Pressure For Increamentioning
confidence: 99%